2019
DOI: 10.1186/s12967-019-2038-5
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreserved mesenchymal stem cells regain functional potency following a 24-h acclimation period

Abstract: Background Mesenchymal stem cells (MSCs) are attractive cell-therapy candidates. Despite their popularity and promise, there is no uniform method of preparation of MSCs. Typically, cells are cryopreserved in liquid nitrogen, thawed, and subsequently administered to a patient with little to no information on their function post-thaw. We hypothesized that a short acclimation period post-thaw will facilitate the recovery of MSC’s functional potency. Methods Human bone-marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 39 publications
4
48
0
Order By: Relevance
“…Antebi et al reported the 24 h post-thaw viability of MSC frozen with 10% DMSO to be ∼80%, highlighting that supplementation with our polyampholyte can achieve the same results but using just a quarter of the [DMSO]. 23 In a clinical context, this is a highly desirable achievement, as lowering the DMSO content of transfused stem cells has been shown to reduce the incidence of adverse clinical side effects 5-fold. 7 Critically, we have reported 24 h post-thaw results as MSCs require 24 h post-thaw to regain function and enable true evaluation of recovery.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Antebi et al reported the 24 h post-thaw viability of MSC frozen with 10% DMSO to be ∼80%, highlighting that supplementation with our polyampholyte can achieve the same results but using just a quarter of the [DMSO]. 23 In a clinical context, this is a highly desirable achievement, as lowering the DMSO content of transfused stem cells has been shown to reduce the incidence of adverse clinical side effects 5-fold. 7 Critically, we have reported 24 h post-thaw results as MSCs require 24 h post-thaw to regain function and enable true evaluation of recovery.…”
mentioning
confidence: 80%
“… 7 Critically, we have reported 24 h post-thaw results as MSCs require 24 h post-thaw to regain function and enable true evaluation of recovery. 23 This point is crucial to show the impact of this work; Zhao et al reported post-thaw viabilities of ∼90% when freezing 3T3 cells with polyampholytes. However, the majority of cells died after 24 h in culture.…”
mentioning
confidence: 92%
“…Cryopreservation has been shown to influence MSCs' therapeutic value with regard to impaired immunosuppressive activities, increased proapoptotic features, and impaired regenerative potential [52][53][54]. More recent studies show that MSCs do maintain their differentiation capacity and also immunomodulatory features after cryopreservation, but that a "reactivation" period of at least 24 h after thawing is beneficial [55]. Our P2 cells after thawing had more than 24 h to "reactivate" before experiments were started.…”
mentioning
confidence: 81%
“…Conversely, T-UC MSCs, in this study, showed above 97% viability of cells with comparable morphology and proliferation compared with the C-UC MSCs even after fresh thawing procedure. Cell viability depends on the thawing method, duration of cold storage, and reagents used [36]. Relatively short storage periods [37] and optimal concentration of DMSO (10%) are crucial factors contributing to high cell viability in cryopreserved conditions [35,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%